DONOR SITE MORBIDITY: A COMPARISON OF THE RADIAL FOREARM FREE FLAP AND ANTEROLATERAL THIGH FREE FLAP - Mehreen Masud Qureshi (Army Medical College Rawalpindi, 2019)
Objective: To compare the donor site morbidity of these two flaps in terms of wound infection, wound dehiscence, skin graft take/primary healing, sensory abnormalities, functional loss and subjective analysis of donor site appearance.